Networked control strategy of dual linear switched reluctance motors based time delay tracking system. (October 2022) - Qiu, Li; He, Lun; Dai, Longcheng; Fang, Chen; Chen, Zihao; Pan, Jianfei; Zhang, Bo; Xu, Ying; Chen, C.R.
Abstract: To reduce the influence of time delay on the tracking performance of a direct-drive motion control system, this paper concentrates on stability analysis and cooperative position tracking control issues for the dual linear switched reluctance motors (LSRMs) system with network-induced time delays. The closed-loop network control system (NCS) is constructed by modeling random and bounded network-induced time delays existing in forward and feedback channels as a discrete-time Markov chain. Incremental time delay information is introduced in Lyapunov functional analysis to satisfy the high-precision movement of master and secondary motors and improve the system control performance. The time delay compensation method is proposed to compensate for the damage to the networked control system caused by random delay. With Lyapunov stability theory and LMI are applied, stability and stabilization conditions with less computational complexity and low conservatism are obtained based on incremental time delay information insertion. Finally, the numerical simulation and the experimental platform of the motor control system are built. Simulation and experiment results demonstrate that the networked control strategy can compensate the negative impact of delay on the tracking performance of LSRMs based motion control system. Highlights: A Lyapunov functional with time delay is constructed, and the stability condition of the proposed networked dual LSRMs system is analyzed. Combining Lyapunov theory, linear matrix inequality technology and Markov stochastic process, the time delay compensation controller for the proposed networked dual LSRMs is designed. Incremental delay compensation and Wirtinger-based inequality are used for stability analysis and control strategy to obtain lower computational complexity and conservativeness. The networked dual LSRMs system with time delay is constructed both on the simulation and physical experiment platform, and the networked control strategy based on time delay compensation is verified from the numerical simulation and physical experiment.